2011
DOI: 10.1111/j.1758-0854.2011.01052.x
|View full text |Cite
|
Sign up to set email alerts
|

Could Exposure to Everyday Green Spaces Help Treat ADHD? Evidence from Children's Play Settings

Abstract: Background: An estimated 4.4 million children in the United States suffer from Attention Deficit/Hyperactivity Disorder (ADHD), and most would benefit from a low-cost, side-effect-free way of managing their symptoms. Previous research suggests that after isolated exposures to greenspace, children's ADHD symptoms are reduced. This study examined whether routine exposures to greenspace, experienced through children's everyday play settings, might yield ongoing reductions in ADHD symptoms. Methods: Data on 421 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 36 publications
3
84
1
3
Order By: Relevance
“…Higher levels of greenness at home and school were associated with improved cognitive development (i.e., better progress in working memory and reduced inattentiveness) in schoolchildren in an observational study in Spain . A number of other studies have similarly demonstrated the positive impact of green space exposure on ADHD and related cognitive symptoms (Faber Taylor and Kuo 2011;Markevych et al 2014). There is also evidence of therapeutic benefits of engaging people with autism with nature (reviewed by Faber Taylor and Kuo 2006).…”
Section: Improved Mental Health and Cognitive Functionmentioning
confidence: 96%
“…Higher levels of greenness at home and school were associated with improved cognitive development (i.e., better progress in working memory and reduced inattentiveness) in schoolchildren in an observational study in Spain . A number of other studies have similarly demonstrated the positive impact of green space exposure on ADHD and related cognitive symptoms (Faber Taylor and Kuo 2011;Markevych et al 2014). There is also evidence of therapeutic benefits of engaging people with autism with nature (reviewed by Faber Taylor and Kuo 2006).…”
Section: Improved Mental Health and Cognitive Functionmentioning
confidence: 96%
“…For instance, Faber Taylor and colleagues (2002) reported that girls, but not boys, with a more natural view from home performed better on assessments of concentration, impulse control, and delay of gratification. Several studies did not report analyses of sex differences (Faber Taylor & Kuo, 2009;Faber Taylor, Kuo, & Sullivan, 2001;Kidwell, 2012;Wells, 2000), and two studies reported no gender differences (Faber Taylor & Kuo, 2011;Kuo & Faber Taylor, 2004). In early childhood, the developmental trajectory of some aspects of executive function varies by sex (Vuontela et al, 2003).…”
Section: Goals Of the Current Studymentioning
confidence: 99%
“…A growing body of evidence suggests that spending time in natural environments can benefit children's attention. For example, parents of children diagnosed with attention deficits (Attention Deficit Disorder or Attention Deficit Hyperactivity Disorder, ADD/ADHD) reported that their children exhibited fewer symptoms of ADHD after their children engaged in outdoor activities in natural environments compared with indoor environments (Kuo & Faber Taylor, 2004), and even compared with outdoor activities in built environments (Faber Taylor & Kuo, 2011). Similarly, children aged 7 to 12 years diagnosed with ADD or ADHD demonstrated improved attention as assessed by the Digit Span Backwards (DSB) after a 20 min walk in a park compared with a 20 min walk in an urban area.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Faber and Kuo studied data from weekly Internet surveys of 421 parents provided information about where their (5 to 18 year old) children played and the severity of their ADHD symptoms that week. The study found that the children who regularly played in natural settings had milder symptoms than the ones who played in an indoor or outdoor built setting (Faber Taylor & Kuo, 2011). A further study involving seventeen 7 to 12 year olds diagnosed with ADHD studied the impacts of outdoor activity settings on concentration levels.…”
Section: A Nature Deficit Disordermentioning
confidence: 99%